The Construction of Memory Layers in “A barrier against the Pacific” and “The Lover” by Marguerite Duras. - RAHMANI, Amina; LOGBI, Hanene (Journal of Human Sciences, 2023)
This article examines the layers of memory in the works of Marguerite Duras, particularly « A barrier against the Pacific » and « The Lover ». We analyze how Duras utilizes memory to address themes such as love, desire, and identity. Our study assesses the influence of different memory layers on readers’ perceptions and underscores Duras’s significance as a writer in the realm of memory. Characters draw from their memories to make sense of their existence, while social and historical dynamics influence their experiences. Duras’s narrative approach creates a dreamlike atmosphere where memories overlap, and her narratives explore the visual and auditory possibilities of expressing the complexities of remembrance.